Pengaruh Good Corporate Governance Terhadap Agresivitas Pajak dengan Voluntary Disclosure Sebagai Variabel Pemoderasi - Pradnyawati, Ni Putu; Suprasto, Herkulanus Bambang (E-Jurnal Akuntansi; Vol 26 No 2 (2019), 2019)
The study was conducted at manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2017 period. Determination of the sample using non probability sampling method with purposive sampling technique. The analysis technique used is Moderated Regression Analysis (MRA). Based on the results of the analysis it was found that audit quality had a negative effect on tax aggressiveness. This explains that audit quality is able to monitor the actions of tax aggressiveness. The better the audit quality of a company, the lower the tax aggressiveness. Three other tests were unable to prove the hypothesis that public ownership negatively affected tax aggressiveness, voluntary disclosure can strengthen the influence of audit quality on tax aggressiveness, and voluntary disclosure can strengthen the influence of public ownership on tax aggressiveness. Keywords: audit quality, public ownership, voluntary disclosure, tax aggressiveness